Enantioselective Cobalt(III)‐Catalyzed C−H Activation Enabled by Chiral Carboxylic Acid Cooperation. (24th October 2018) - Pesciaioli, Fabio; Dhawa, Uttam; Oliveira, João C. A.; Yin, Rongxin; John, Michael; Ackermann, Lutz
Abstract: The enantioselective cobalt(III)‐catalyzed C−H alkylation was achieved through the design of a novel chiral acid. The cobalt(III)‐catalyzed enantioselective C−H activation was characterized by high position‐, regio‐ and enantio‐control under exceedingly mild reaction conditions. Thereby, the robust cooperative cobalt(III) catalysis proved tolerant of valuable electrophilic functional groups, including hydroxyl, bromo, and iodo substituents. Mechanistic studies revealed a considerable additive effect on kinetics and on a negative non‐linear‐effect.